Hubungan Antara Motivasi Berprestasi dan Dukungan Guru Terhadap Student Engagement pada Siswa SMA di Kota Padang - Alya Nur Afiffah; Devi Rusli (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
and competencies; however, they exhibit lower levels of engagement. Student engagement is influenced by internal and external factors, such as achievement motivation and teacher support. This study aims to explore the relationship between achievement motivation and teacher support in relation to student engagement among high school students in Padang City. The sample of this study included 206 students of SMAN 5 Padang selected through a simple random sampling method. Three measurement instruments were used in this study: the Student Engagement Scale (SES), the Achievement Motivation Scale (AMS), and the Child and Adolescent Social Support Scale (CASSS) level two. Multiple correlation analysis techniques were used for testing, which revealed a positive correlation between achievement motivation and teacher support with student engagement, characterized by moderate correlation strength. This indicates that increased achievement motivation and teacher support are associated with higher student engagement. Additional research exploring students' socioeconomic status (SSE) and intellectual intelligence (IQ) is recommended in this study.